Analysis of age and spatially dependent population model: Application to forest growth. (December 2020) - Deng, Keng; Webb, Glenn F.; Wu, Yixiang
Abstract: In this paper, we consider an age-structured population model with diffusion. We first establish a comparison principle. We then apply the comparison principle to show the existence and uniqueness of solutions by constructing monotone sequences of weak upper and lower solutions. We also use the comparison principle to study the long-time behavior of the solution and present extinction and boundedness results under certain conditions on the parameters in the model. Additionally, as an example of its application, we apply the model to describe the dynamics of a forest population.